Analisis Sistem Informasi Website To Do List Menggunakan Metode Agile - Eko Andri Wibowo (PT Jurnal Cendekia Indonesia, 2025)
Advances in information technology have facilitated the birth of various applications designed to increase user productivity, one of which is a web-based To Do List application. This study aims to evaluate the information system of the To Do List application using the Agile method approach. The selection of the Agile method is based on its ability to provide high flexibility in the software development process through an iterative approach and ongoing team collaboration. In implementing this study, the development stages were carried out systematically starting from planning, interface design, feature implementation, to testing system functionality. The research findings indicate that the application of the Agile method is able to increase the system's ability to adapt to user needs dynamically, accelerate the development process, and ensure that each feature functions as expected. The results of this study are expected to be a reference for the development of similar information systems that prioritize an adaptive and user-centered approach.